Pattern grading design for women's batik fabric in Terengganu, Malaysia: a preliminary study - Che Ya, Mohamad Shukri; Shaari, Nazlina; Mansor, Noranita (Human Resource Management Academic Research Society, 2022)
The Malaysian batik manufacturing industry is seen as an industry that has a contributor to the national economy. However, to maintain and increase the Malaysian batik economy, batik fabric manufacturing must move in line with the current manufacturing methods and technology. Therefore, the existing batik fabric needs to be improved in terms of manufacturing, including pattern grading design. This study aims to identify the preliminary analysis of the common pattern grading scheme for women's existing batik cloth in Terengganu, Malaysia. In order to gather data for this study, observations and interviews were used as the approach. Eight batik experts were interviewed for the study, and three batik markets and craft fairs in Terengganu were chosen for observation. The findings indicate that the current batik fabric needs to be developed into a pattern grading design to keep up with modern techniques and technology while minimizing the amount of extra cloth disposed of.